Body composition and physical activity levels in overweight and obese pregnant women during early pregnancy in Beijing city - Jing LIANG; Jianqiang LAI; Yue TENG; Yan ZHANG; Ning LIANG; Shan DONG; Zengxu TANG; Chao SONG (Zhongguo gonggong weisheng)
ObjectiveTo analyze the current status of body composition, sedentary time, and physical activity levels in overweight and obese pregnant women during early pregnancy, and to explore the influencing factors of visceral fat area (VFA), so as to provide a scientific basis for preventing excessive weight gain and improving health status in this population. MethodsThis cross-sectional study recruited 154 overweight and obese women in early pregnancy (gestational age ≤14 weeks) from the nutrition clinic of Haidian Maternal and Child Health Hospital in Beijing city from November 2023 to May 2024. Demographic characteristic, physical activity, and dietary information were collected through a basic health status questionnaire, the International Physical Activity Questionnaire (IPAQ), and a Food Frequency Questionnaire (FFQ). Body composition was measured based on bioelectrical impedance analysis. Spearman correlation analysis was used to analyze the correlation between body composition-related indicators and VFA. Multiple logistic regression and generalized additive models were used to analyze the influencing factors of VFA. ResultsA total of 131 valid questionnaires and 154 body composition reports were collected, with effective rates of 85% and 100%, respectively. 45.04%of the pregnant women had low physical activity levels, and 54.96%had moderate or higher levels. The median (interquartile range) of body composition-related indicators were as follows: VFA, 136 (116–157) cm2; waist-to-hip ratio, 0.93 (0.90–0.96); body weight, 72 (67–76) kg; body fat, 27 (25–31) kg; basal metabolic rate (BMR), 5 522 880 (5 284 392–5 799 024) J; body mass index (BMI), 27 (26–29); muscle mass, 41 (36–41) kg; and body fat percentage, 38 (36–41)%. Sedentary time was 400 (240–480) min/d. Multiple logistic regression analysis showed that after adjusting for confounding factors such as age, dairy, refined grains, and fruit and vegetable intake, excessive BMI was a risk factor for higher VFA (OR=2.7, 95%CI: 1.602–2.951). Generalized additive models showed that sedentary time and physical activity level had statistically significant effects on VFA (P<0.05). ConclusionsInsufficient physical activity levels and prolonged sedentary time in some overweight and obese pregnant women during early pregnancy should be addressed. Excessive BMI is a major risk factor for visceral fat accumulation. Overweight and obese pregnant women should arrange sedentary and exercise time appropriately according to their own circumstances, regularly monitor their body composition, and effectively prevent excessive weight gain during pregnancy and improve their overall health.